Antihypertensive Effect Of Amlodipine In Co-Administration With Omeprazole In Patients With Hypertension And Acid-Related Disorders: Cytochrome P450-Associated Aspects - Dorofeeva MN; Shikh EV; Sizova ZM; Tarasenko AV; Denisenko NP; Smirnov VV; Ryzhikova KA; Sozaeva ZA; Grishina EA; Sychev DA (Pharmacogenomics and Personalized Medicine, 2019)
Margarita N Dorofeeva,1 Evgenia V Shikh,2 Zhanna M Sizova,1 Alisa V Tarasenko,3 Natalia P Denisenko,4,5 Valeriy V Smirnov,6,7 Kristina A Ryzhikova,4 Zhannet A Sozaeva,4 Elena A Grishina,4 Dmitriy A Sychev5 1Department of Social Expertise, Urgent and Outpatient Therapy, First Moscow State Medical University (Sechenov University), Ministry of Healthcare, Moscow, Russia; 2Department of Clinical Pharmacology and Propedeutics of Internal Diseases, First Moscow State Medical University (Sechenov University), Ministry of Healthcare, Moscow, Russia; 3Medicine of the Future, First Moscow State Medical University (Sechenov University), Ministry of Healthcare, Moscow, Russia; 4Research Institute, Russian Medical Academy of Continuous Professional Education, Ministry of Healthcare, Moscow, Russia; 5Department of Clinical Pharmacology and Therapy, Russian Medical Academy of Continuous Professional Education, Ministry of Healthcare, Moscow, Russia; 6Department of Pharmaceutical and Toxicological Chemistry, First Moscow State Medical University (Sechenov university), Ministry of Healthcare, Moscow, Russia; 7Laboratory of Clinical Pharmacology, National Research Centre - Institute of Immunology, Federal Medical Biological Agency, Moscow, RussiaCorrespondence: Natalia P DenisenkoResearch Institute, Russian Medical Academy of Continuous Professional Education, Ministry of Healthcare, Barrikadnaja Street, 2/1, Moscow 125993, RussiaTel +7 495 945 81 39Email natalypilipenko3990@gmail.comBackground: CYP2C19 and CYP3A are the main enzymes involved in omeprazole metabolism, while CYP3A is the principal enzyme family for amlodipine biotransformation. Concomitant use of these drugs in patients with hypertension and acid-related disorders (ARD) might lead to drug–drug interaction.Purpose: The aim of the study was to find if adding omeprazole for treating ARD to amlodipine long-term therapy of hypertension influenced blood pressure of CYP2C19 polymorphism carriers.Patients and methods: Fifty-one patients diagnosed with hypertension and ARD were enrolled in the study. Evaluation of antihypertensive therapy was performed by office (OBPM) and ambulatory (ABPM) blood pressure monitoring. Peripheral venous blood was collected for DNA extraction and real-time polymerase chain reaction was performed for CYP2C19*2G681A (rs4244285), CYP2C19*3G636A (rs4986893) and CYP2C19*17C−806T (rs12248560) polymorphisms analysis.Results: Of 51 patients there were 21 extensive metabolizers (EMs), 18 ultrarapid metabolizers (UMs) and 12 intermediate metabolizers (IMs). The results of OBPM showed that antihypertensive effect was significantly more pronounced in IMs compared to EMs or UMs and the average group value in the following parameters: average office systolic blood pressure (BP), dynamics of the average office systolic BP. According to dynamics of diastolic BP, the antihypertensive effect was also significantly higher in IMs than in UMs and the average group value. The results of ABPM revealed that there was a significantly more pronounced antihypertensive effect in IMs compared to all other analyzed groups according to the dynamics of both daytime systolic and 24 hr diastolic BP. The average daytime diastolic BP and its dynamics, the average 24 hr systolic BP and its dynamics were higher in IMs compared to EMs and UMs.Conclusion: Adding omeprazole to long-term amlodipine therapy in patients with hypertension and ARD may lead to a significantly more pronounced antihypertensive effect in patients genotyped CYP2C19 IMs.Keywords: CYP2C19, CYP3A, pharmacogenetics, proton pump inhibitor